Analisis Interkoneksi Jaringan IPv6 Terhadap IPv4 Dengan Tunnel Broker Berbasis Web - Michael Sitorus; Neneng Rachmalia Feta (BRITech, Jurnal Ilmiah Ilmu Komputer, Sains dan Teknologi Terapan, 2020)
Which is IPv4 only 32 bits (4 bytes) there is a weakness in the configuration is manually implemented or by Dinamyc Host Configuration Protocol (DHCP). DHCP is use for allocation convenience of IP (Internet Protocol) addresses in a network dynamically. The addresses total can be achieve 4.294.967.296 addresses. Even though the total address reaches 4 billion, the real it is not up to 4 billion addresses, because there are some limitations or restrictions that make the addressing few, so as the implementation only achieve a few hundred million. In this research, IPv6 as a new standard is capable to interconnect with IPv4 because IPv6 is not compatible in IPv4. For that need a certain mechanism let IPv6 can interconnect with IPv4. The methodology used by using a transition mechanism from IPv4 to IPv6 such as Dual IP Stack, Tunneling, and Protocol Translation. The results of research will tunneling caption IPv6 over IPv4 make IPv6 package with IPv4 package in the encapsulation process, so that IPv6 package treated as IPv4 package others. Then easily the IPv6 package can be sent through IPv4 network using a tunnel broker.